2012
DOI: 10.5923/j.microbiology.20120202.04
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Encoded Bacteriocins: Their Functional Insight and Applications

Abstract: are the secretory proteins which inhibit the growth of closely related bacteria. Their transcriptions are regulated under different environmental conditions and have different modes of action which includes non specific DNase activity, specific RNase activity, pore forming and inhibition of murein synthesis in bacteria. In this article we have summarized the genetic organization, regulation, structural organization, reception and functional activities of ribosomal encoded bacteriocins only and does not discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Comparisons of specific activity of inulosucrase cloned into periplasmic expression vector, transformed and expressed in E. coli 16 and E. coli BL21 demonstrated that extracellular expression is achieved only in colicin producing microorganism. Various reports suggested that BRP protein is responsible for the release of colicin such as colicin A, E1, E2, K, N, U, and Y into the extracellular medium (Cascales et al, 2007;Sommer et al, 2010;Singh et al, 2012). There are reports that extracellular secretion could be achieved in E. coli strain by coexpression of a lysis-promoting protein (Sommer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons of specific activity of inulosucrase cloned into periplasmic expression vector, transformed and expressed in E. coli 16 and E. coli BL21 demonstrated that extracellular expression is achieved only in colicin producing microorganism. Various reports suggested that BRP protein is responsible for the release of colicin such as colicin A, E1, E2, K, N, U, and Y into the extracellular medium (Cascales et al, 2007;Sommer et al, 2010;Singh et al, 2012). There are reports that extracellular secretion could be achieved in E. coli strain by coexpression of a lysis-promoting protein (Sommer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Sommer et al (2010) constructed a plasmid which contains bacteriocin release proteins (BRP) that allow secretion of recombinant protein from the periplasm into the culture medium (Sommer et al, 2010). It was known that BRP or lysis proteins are responsible for the release of colicins such as A, E1, E2, K, N, U, and Y (Cascales et al, 2007;Singh et al, 2012). Previously, we had reported E. coli 16 isolated from rat fecal matter to possess characteristic such as acid tolerance, antibiotic sensitivity, no pathogenicity and antimicrobial activity against the members of Enterobacteriacae family.…”
Section: Introductionmentioning
confidence: 99%
“…Their structure comprises of three distinct domain organizations: (i) a domain involved in recognition of specific receptor R, (ii) a domain involved in translocation T, and (iii) a domain responsible for their toxic activity C. Molecular mass of ribosomal encoded bacteriocins vary from ~25 to 80 kDa and are broadly classified into two groups, group A and B, based on their cross-resistance [ 4 ]. These proteins have received increasing attention due to their potential use as preservatives in the food industry or in the therapeutic applications for clinical usage [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriocins are small and cationic antimicrobial peptides, ribosomally synthesized by lactic acid bacteria (LAB) (Singh, Ghosh, 2012), with antilisterial activity (Papagianni, Sergelidis, 2015) and many industrial applications (Papagianni, 2003). The industrial importance of LAB is further demonstrated by their status generally recognized as safe (GRAS) (Fan, Song, 2013).…”
Section: Introductionmentioning
confidence: 99%